Comparison of body composition and physical performance between college and professional basketball players - Delgado-Floody, P.; Caamaño-Navarrete, F.; Carter-Thuillier, B.; Gallardo-Fuentes, F.; Ramirez-Campillo, R.; Cresp Barria, M.; Latorre-Román, P.; Garcia-Pinillos, F.; Martinez-Salazar, C.; Jerez-Mayorga, D. (Archivos de medicina del deporte, 2017)
Introduction: The body composition, anthropometrics and physical performance of basketball players are fundamental for their practice of the sport. The purpose of this study was to evaluate and compare body composition and physical performance among college and professional basketball players.